Evidence-Based Practice in Psychology Fails to Be Tripartite: A Conceptual Critique of the Scientocentrism in Evidence-Based Practice in Psychology - Berg, Henrik (Frontiers in Psychology, 2019)
This paper criticises evidence-based practice in psychology for not actually being a tripartite model. According to the American Psychological Association evidence-based practice in psychology is defined as the integration of the best available research with clinical expertise in the context of patient characteristics, culture, and preferences. Nonetheless, evidence-based practice in psychology fails to be a tripartite model because it is defined by science alone. This paper aims at explaining why this conflation may have come about. It also shows why clinical expertise and patient preferences should be defined extra-scientifically.